Liminal politics: Performing feminine difference with Hélène Cixous. Issue 3 (August 2018) - Varino, Sofia
As one of the most influential feminist theorists in Western academic circles, Hélène Cixous is often associated with écriture feminine (feminine writing), a term she coined in 1977, and with a fluid, poetic style both in her essays and in her fiction. This article investigates how Hélène Cixous uses the concept of the 'feminine' in her plays as a container for heterogeneity, liminality and difference, mobilizing it to animate feminist strategies that interrupt male, white and/or hegemonic forms of subjectivity. If for Cixous the practice of feminine writing is fundamentally characterized by the desire to create a mode of expression in which (gendered, embodied, racial) difference and otherness would retain their alterity, in dramatic writing she found an especially conducive medium for the realization of that desire. This article examines Cixous's anti-realist postdramatic works, from her first produced play Portrait of Dora (1976) to her works for Ariane Mnouchkine's Théâtre du Soleil, in the context of a feminist aesthetics of estrangement, and considers how her plays enact feminist theory's own movement away from the psychoanalytical discourses of the 1970s and 1980s to postcolonial and materialist critiques. The article employs a range of intersectional critical methodologies for situating Cixous's dramatic writing within a broader feminist praxis, using the work of feminist performance scholars like Elin Diamond, Rebecca Schneider and Jill Dolan to consider the liminal Other as a precarious feminine figure that Cixous re-inscribes into discourse. Feminine writing, the progressive movement away from realism towards postdramatic theatre, and Cixous's artistic collaboration with Mnouchkine are each considered as feminist strategies towards a rendition of the subject that can reiterate its otherness on stage. The central argument is that it is the enactment of these strategies in live performance that makes Hélène Cixous's concept of femininity as liminal difference so relevant for feminist politics today.